2011
DOI: 10.1126/science.1201476
|View full text |Cite
|
Sign up to set email alerts
|

A Sorting Platform Determines the Order of Protein Secretion in Bacterial Type III Systems

Abstract: Bacterial type III protein secretion systems deliver effector proteins into eukaryotic cells in order to modulate cellular processes. Central to the function of these protein delivery machines is their ability to recognize and secrete substrates in a defined order. Here, we describe a mechanism by which a type III secretion system from the bacterial enteropathogen Salmonella enterica serovar Typhimurium can sort its substrates prior to secretion. This mechanism involves a cytoplasmic sorting platform that is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
308
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(325 citation statements)
references
References 35 publications
16
308
1
Order By: Relevance
“…It has been previously shown that there is a hierarchy in the type III secretion process so that different proteins are engaged at different times (10,29). Proteins necessary for the assembly of the needle and inner rod substructures of the needle complex are engaged first.…”
Section: Prgj Mutant Strains With Aberrant Needle Length Are Able To mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown that there is a hierarchy in the type III secretion process so that different proteins are engaged at different times (10,29). Proteins necessary for the assembly of the needle and inner rod substructures of the needle complex are engaged first.…”
Section: Prgj Mutant Strains With Aberrant Needle Length Are Able To mentioning
confidence: 99%
“…However, the hierarchy in the secretion process extends beyond needle complex assembly because the protein translocases, which mediate the passage of effectors through the target host cell membrane, must be secreted before the effector proteins themselves. Indeed, a cytoplasmic sorting platform has been shown to be critical to the establishment of the secretion hierarchy (10). We examined the PrgJ mutants for their ability to secrete proteins within the different hierarchical categories of type III secretion.…”
Section: Prgj Mutant Strains With Aberrant Needle Length Are Able To mentioning
confidence: 99%
See 1 more Smart Citation
“…During infection of vertebrate cells, the protozoan pathogen Toxoplasma gondii secretes effectors by sequential triggering of three distinct parasite organelles known as micronemes, rhoptries, and dense granules, at different phases during its intracellular growth (Carruthers and Sibley 1997). Bacterial enteropathogen Salmonella enterica uses a sorting platform involving chaperone proteins to sort and load the effectors to be secreted in a defined order via T3SS (Lara-Tejero et al 2011). In bacterial plant pathogens, T3SS is also used to deliver effectors into plant cells in a regulated manner.…”
Section: Temporal Aspects Of Pathogen Deployment Of Effectorsmentioning
confidence: 99%
“…This implies that InvE may transiently interact with the membrane or membrane-associated proteins of the SPI-1 T3SS (Kubori & Galán, 2002). Recently, Lara-Tejero et al (2011) reported that the secretion hierarchy between the translocases and effector proteins in the SPI-1 T3SS is established by a large complex that includes the SpaO-OrgA-OrgB sorting platform. It has also been determined that the T3SS-associated chaperones are responsible for the proper targeting of their cognate substrates to the sorting complex.…”
Section: Introductionmentioning
confidence: 99%